Penguatan Kompetensi Guru Biologi Melalui Pelatihan Teknik Kultur Jaringan Tumbuhan Di Kabupaten Tanggamus, Lampung - Endang Nurcahyani; Sumardi; Yulianty; Dewi Sulistyawati (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Biology teachers' competence in utilizing laboratory facilities as learning media plays an important role in developing students' scientific skills. However, the application of plant tissue culture techniques as a practical component of biotechnology learning is still limited in many secondary schools. This community service program aimed to strengthen the competence of senior high school Biology teachers through plant tissue culture training conducted at SMAN 1 Wonosobo, Tanggamus Regency, Lampung. The program consisted of lectures, demonstrations, hands-on laboratory practice, and learning evaluation using pre-test and post-test assessments. The training materials covered the basic principles of plant tissue culture, sterilization techniques, culture media preparation, explant inoculation, subculturing, and plantlet maintenance. The evaluation results showed that the participants' average knowledge score increased from 39.8% before the training to 88.0% after the training, representing an improvement of 48.2 percentage points. These findings indicate that the training program was effective in enhancing teachers' knowledge and practical skills in plant tissue culture techniques. The improved competence is expected to support the implementation of laboratory-based biology learning and promote the development of students' scientific skills in secondary schools.